(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents a comparative etymological analysis of business terms in English and Uzbek. As English has become the global business language, many English terms have been introduced into other languages, including Uzbek. This report presents an etymological analysis of business terms in English and Uzbek, examining their origin, meaning, and usage. English terms are often borrowed from Latin, French, and other languages, while Uzbek terms are based on Turkic roots or adopted from other languages. This article aims to study terms that play an important role in the global economy, analyze their origin, and the process of their development, and will serve as a useful resource for linguists, economists, and business professionals.